Associations between sleep problems and posttraumatic stress symptoms, social functioning, and quality of life in refugees with posttraumatic stress disorder - Schumm, Hannah; Steil, Regina; Lechner-Meichsner, Franziska; Morina, Nexhmedin; Weise, Cornelia; Mewes, Ricarda; Kuck, Sascha; Reuter, Julia; Giesebrecht, Julia; Cludius, Barbara; Ehring, Thomas (Journal of Traumatic Stress, 2023)
Many patients with posttraumatic stress disorder (PTSD) suffer from sleep problems, leading to impairments in social functioning and quality of life. Refugees are at high risk for sleep problems due to stressful life circumstances and a high PTSD prevalence. However, limited data on the frequency of sleep problems in refugees with diagnosed PTSD exist. This study examined the frequency of sleep problems in refugees with PTSD and their associations with symptoms of PTSD. Additionally, we investigated the contribution of sleep problems to social functioning and quality of life. Participants (N = 70) were refugees from different countries of origin currently living in Germany. All participants met the criteria for PTSD and completed measures of PTSD symptom severity, subjective sleep problems, social impairment, and quality of life. There was a very high frequency of sleep problems in the sample (100%), and sleep problems were significantly associated with both clinician-rated, r =.47, and self-rated, r =.30, PTSD symptom severity after controlling for overlapping items. Contrary to expectations, sleep problems did not predict social impairment, d = 0.16, nor quality of life, d = 0.13, beyond the effect of other PTSD symptoms. The findings highlight the widespread frequency of sleep problems among refugees. Future studies should assess the causal nature of the association between sleep problems and measures of psychosocial functioning in more detail and examine its dynamic change over time.
CRIS-Team Scopus Importer:2024-03-27